140k views
3 votes
2x - y = 11
6x – 3y = 15
solve for x and y using elimination

User Shrikey
by
6.3k points

1 Answer

6 votes

Answer:

Explanation:

Given the simultaneous equation

2x - y = 11. Equation 1

6x – 3y = 15. Equation 2

Using elimination method

Multiply the coefficient of x in equation 1 (which is 2) to equation 2. Also, multiply the coefficient of x in equation 2 (which 6) to equation 1. By doing this we are going to eliminate x

2x - y = 11. × 6 Equation 1

6x – 3y = 15. ×2 Equation 2

12x-6y=66. Equation 3

12x-6y=30. Equation 4

Subtract equation 4 from 3

Then (12x-6y) - (12x-6y) =66 -30

0=36

Which is not possible

Then the system has no solution, it has no solution at all. Because 0 is not equal to 36. If has been 0 equals to 0, then we may many solutions for simultaneous equation.

User EsmaeelE
by
5.8k points